Morquio syndrome: A radiological diagnosis - Sadhanandham Shrinuvasan; Ranganathan Chidambaram (Wolters Kluwer Medknow Publications, 2015)
Mucopolysaccharidoses (MPS) are a family of inherited metabolic diseases that results from the deficiency of lysosomal enzymes involved in the degradation of the glycosaminoglycans (MPS). We report here a 7-year-old female child who presented with complaints of short stature, skeletal deformities, and difficulty in walking with normal intelligence. A clinical diagnosis with differential diagnosis of achondroplasia/rickets was considered. Skeletal survey showed radiological features characteristic of Morquio syndrome (MPS IV) which lead to diagnosis in this case.